Epidemiological Analysis of Peripartum Hysterectomy Across 9 European Countries. Issue 3 (September 2021) - Kallianidis, A.F.; Maraschini, A.; Danis, J.; Colmorn, L.B.; Deneux-Tharaux, C.; Donati, S.; Gissler, M.; Jakobsson, M.; Knight, M.; Kristufkova, A.; Lindqvist, P.G.; Vandenberghe, G.; et al.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:1364–1373) Peripartum hysterectomy is typically performed in cases of severe obstetric complications such as massive obstetric hemorrhage, sepsis, uterine rupture, or abnormally invasive placenta. It is an outcome of interest in obstetric surveillance due to its classification by the World Health Organization as a near-miss criteria. The primary aim of this study was to compare rates of and indications for peripartum hysterectomy within high-income countries. Secondarily, authors aimed to describe hysterectomy indications and prevalence of peripartum hysterectomy based on country and other categories of birth including previous cesarean delivery (CD).